The Whiteboard Revolution: Illuminating Science Communication in the Digital Age. Issue 4 (April 2016) - Mar, Florie Anne; Ordovas-Montanes, Jose; Oksenberg, Nir; Olson, Alexander M.
Abstract : Journal-based science communication is not accessible or comprehensible to a general public curious about science and eager for the next wave of scientific innovation. We propose an alternative medium for scientists to communicate their work to the general public in an engaging and digestible way through the use of whiteboard videos. We describe the process of producing science whiteboard videos and the benefits and challenges therein.